Dashboard settings design in SVARA using user-centred design method - Muhammad Yusril Helmi Setyawan; Rolly Maulana Awangga; Rezka Afriyanti (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
SVARA is the first Social Media audio application in Indonesia developed by PT. Zamrud Teknologi Khatulistiwa. At present, this application does not have feature settings to display content and other basic settings on the user's side. This situation results in users not having the role to manage the appearance of the dashboard according to their preferences. Settings are done entirely by administrators using scripts and must take APIs with regular PHP scripts. And this is very troublesome. So to give a role to the view of user management, the application needs to be made a dashboard setting feature as a follow-up. Through this paper, the researchers propose designing this dashboard feature using the User-Centered Design (UCD) method. The design results show that this method has a positive correlation with user involvement support in the application development process.